The Effectiveness of Socialization-media in Improving the Knowledge of Children and Teenager toward Cigarette in Denpasar, Bali - Ida Ayu Jasminarti Dwi Kusumawardani (Journal of Global Pharma Technology, 2016)
Background: Prevalence of children and teenagers smoker in Indonesia was more than 45%. This shows the gap between results and efforts of the Indonesian government to reduce tobacco cigarette consumption rate through various programs. Method: Aim of this study was to determine the level of children and teenager knowledge about cigarettes and to measure the effectiveness of socialization media improving their knowledge. This research was held in SMP Negeri 10 Denpasar and SD No. 12 Padangsambian. Design of study was cross-sectional experimental with cluster sampling. The sample size was 203 subjects divided into six groups. The study consists of a pre-test, intervention, and post-test. Level of knowledge about cigarette was determined by questionnaire and divided into 3 levels (good, average, and poor). Interactive communication was given to three groups of students, and the other got advertisement video as an intervention. Result: The overall level of knowledge among children and teenager was good (50.2%), average (37.4%), and poor (12.3%). Level of knowledge among SD No. 12 Padangsambian students was good (42.1%), average (42.8%), and poor (15.2%). While in SMPN 10 Denpasar 70.7% of them was good, average (24.1%), and poor (5.2%). There was no significant difference between pre-test and post-test in the advertisement video intervention group (P>0.05). An increasing number of students with good knowledge was found in interactive communication intervention such as: group I (58%; p <0.05), group II (21.2%; p <0.05), group III (23.2%; p <0.05). Conclusion: Interactive communication could be used as media socialization to increase the knowledge of children and teenager about cigarettes and its negative impact on human health.Keywords: Cigarette, Knowledge, Socialization, Media, Children, Teenager.